The Risk of Preterm Birth in Pregnancies With Fetal Anomalies [11Q]. (May 2017) - Berger, Victoria; Moghadassi, Michelle; Gosnell, Kristin; Sparks, Teresa; Velez, Juan Gonzalez; Norton, Mary
Abstract : INTRODUCTION: To examine the relationship between congenital fetal anomalies and rates of preterm birth (PTB). METHODS: Retrospective study of singleton pregnancies with fetal anomalies, delivered at greater than or equal to 24 weeks at our institution between 2007 and 2015. Our primary outcomes were any PTB and spontaneous PTB (both less than 37 weeks). Anomalies were classified as: cardiac, congenital diagrammatic hernia (CDH), gastrointestinal (GI, including abdominal wall defects), genitourinary (GU), central nervous system (CNS), sacrococcygeal teratoma (SCT), musculoskeletal (MSK), neck mass, and multiple. Chi square and Fisher's exact tests were used to compare proportions, and multivariate logistic regression adjusted for potential confounders. RESULTS: Among 728 pregnancies, the mean gestational age at delivery was 36.8 ± 3.3 weeks. Twenty-nine percent were delivered preterm, and 15.0% were delivered after spontaneous preterm birth (sPTB) specifically. GI anomaly was associated with a 2.62 fold increased odds of sPTB (95% CI 1.52-4.53), while SCT anomaly was associated with 4.50 fold increased odds of the same (95% CI 1.26-16.05). Considering any PTB, there was a 4.81 fold increased odds (95% CI 2.86-8.09) with GI anomaly, and a 3.66 fold increased odds (95% CI 1.06-12.64) with neck mass, adjusting for maternal age, race, BMI, tobacco and substance use. CONCLUSION: Nearly one third of pregnancies with fetal anomalies do not reach term, and the risk of preterm birth varies by anomaly. Increased odds of sPTB were seen with GI anomalies and SCT, and increased odds of any PTB were seen with GI anomalies and neck masses.